2012
DOI: 10.1111/j.1745-7599.2012.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Low-calorie diet induced weight loss may alter regulatory hormones and contribute to rebound visceral adiposity in obese persons with a family history of type-2 diabetes

Abstract: Clinicians may need to revise recommendations for using low-calorie diets to achieve weight loss. Diet-induced weight cycling may contribute to dysregulation of metabolism and have long-term detrimental consequences for accumulation of visceral adipose tissue. The likelihood of success is low, with high dropout rates, and those patients who achieve weight loss are very likely to regain it. Thus, the perceived short-term benefits of calorie-restricted diets in this population likely do not outweigh the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Moreover, no study showed an increase in adiponectin due to a given procedure not also possibly explained by weight loss. The only studies which did not show a change in adiponectin were one showing a decrease in adiponectin after medical weight loss (85) and a study of duodenal-jejunal bypass in which the surgical group did not show a significant change in fat mass or BMI (86). It thus seems most likely that adiponectin production is increased secondary to weight loss in all procedures, since it is increased by weight loss of any kind, including medical weight loss.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, no study showed an increase in adiponectin due to a given procedure not also possibly explained by weight loss. The only studies which did not show a change in adiponectin were one showing a decrease in adiponectin after medical weight loss (85) and a study of duodenal-jejunal bypass in which the surgical group did not show a significant change in fat mass or BMI (86). It thus seems most likely that adiponectin production is increased secondary to weight loss in all procedures, since it is increased by weight loss of any kind, including medical weight loss.…”
Section: Resultsmentioning
confidence: 99%
“…These studies provided discrepant results with some publications suggesting a disproportional regain in total [2][3][4] or abdominal fat mass [2,5], whereas others found no adverse effect of weight cycling on obesity [6] or body fat distribution [7,8] (for a review, see [9 & ]). The current review investigates whether methodological differences regarding the precision and validity of the body composition technology could contribute to these discrepancies.…”
Section: Introductionmentioning
confidence: 94%
“…By contrast with weight gain in women, body fat accumulates predominantly at the extremities . Knowledge on normal gender‐specific partitioning of lean and FM is important because a redistribution of body fat to the truncal or visceral compartments has been proposed to occur during weight regain (, see next section).…”
Section: Introductionmentioning
confidence: 99%